Design of home load management system for load rationing in Pakistan. Issue 3 (20th October 2020) - Butt, Muhammad Bilal; Dilshad, Saad; Abas, Naeem; Rauf, Shoaib; Saleem, Muhammad Shoaib
Abstract: The fast‐growing electricity demand in Pakistan and other developing countries has posed a severe challenge to electricity distribution systems. Indeed, most of the utility companies have to follow a trend of load shedding to face this difficulty. Load shedding is the "art" of managing the load demand by shedding loads in critical situations where the demand is higher than the total generation to avoid system failure. Although electricity utilities are suggesting consumers reduce the load during peak hours in their monthly bills, the consumers are not willing or aware of this. It is clear how tedious and tiresome it is to remind the customers what the peak hours are, and manually switch off/on the heavy load during peak and off‐peak hours. The estimated cost of the system is around 43$ and 28$ with and without Global System for Mobile Communications module for message notification. Moreover, the distribution feeder has a specific capacity to bear the load in peak hours after this is automatically shut down the whole feeder. In this paper, the simulation analysis of a single‐family house is performed for automatic load reduction during peak hours in Proteus software. A hardware prototype is then designed and applied so as to validate the proposed control system. The results show that the proposed scheme allows for an efficient peak shaving during peak hours. For some typical domestic and commercial consumers, the financial benefits are also calculated. It is concluded that the payback period of this device is almost 1 month if it reduces 50% of load during the 4‐hour peak time. The proposed system may be implemented as a single additional tool/span is already available energy meters and may quickly be adopted by electric utilities of developing countries to avoid the load shedding trend. Abstract : We report the design and implementation of a load rationing system that allows for load shedding management. The simulation analysis of a single‐family house is performed for automatic load reduction during peak hours in Proteus software. A hardware prototype is designed and applied so as to validate the proposed control system. The results show that the proposed scheme allows for an efficient peak shaving during peak hours.